Fractional Flow Reserve for Intermediate Coronary Artery Stenosis in Nepal
Background and Aims: : Coronary angiogram detects anatomical lesion, however, has limited ability to assess physiological significance. Fractional flow reserve is used to determine functional significance of stenosis and is measured by the ratio of mean distal coronary pressure to mean aortic pressure during maximum hyperemia. Recently, fractional flow reserve was started in Nepal. This study intends to explore the extent of determination of hemodynamic significance of intermediate coronary stenosis by fractional flow reserve, thereby guiding revascularization. Methods: Consecutive patients with intermediate lesion undergoing fractional flow reserve from July 2014 to March 2015 were included, if fractional flow reserve ?0.80 then considered to be significant and need for revascularization determined. The study subjects were divided into two groups, one having physiologically significant stenosis and another with physiologically non significant lesion and followed up to three months. Results: Total forty four patients had fractional flow reserve done in fifty eight intermediate coronary artery lesions. The age ranged from 33 to 78 with the mean age of 58.25